2018
DOI: 10.3390/app8040495
|View full text |Cite
|
Sign up to set email alerts
|

An Ensemble Based Evolutionary Approach to the Class Imbalance Problem with Applications in CBIR

Abstract: Abstract:In order to lower the dependence on textual annotations for image searches, the content based image retrieval (CBIR) has become a popular topic in computer vision. A wide range of CBIR applications consider classification techniques, such as artificial neural networks (ANN), support vector machines (SVM), etc. to understand the query image content to retrieve relevant output. However, in multi-class search environments, the retrieval results are far from optimal due to overlapping semantics amongst su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 53 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…We can use the recognition accuracies in test phase as a given PFI is first converted into MVAHF images oriented at 0 ∘ , 10 ∘ , 20 ∘ , and 30 ∘ . Then, each of the mentioned MVAHF images is classified against the gallery and leads to four recognition accuracies which are subsequently used to compute the weights in equation (5). This procedure is similar as employed for each of the training images in the training phase.…”
Section: D-mvahf-based Face Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…We can use the recognition accuracies in test phase as a given PFI is first converted into MVAHF images oriented at 0 ∘ , 10 ∘ , 20 ∘ , and 30 ∘ . Then, each of the mentioned MVAHF images is classified against the gallery and leads to four recognition accuracies which are subsequently used to compute the weights in equation (5). This procedure is similar as employed for each of the training images in the training phase.…”
Section: D-mvahf-based Face Identificationmentioning
confidence: 99%
“…The matching score matrix was again normalized as using the min-max rule as given in equation (3). (5) The normalized matching scores obtained from were utilized in the Softmax layer of the AlexNet to compute the final recognition accuracies. (6) The whole process was repeated to classify MVWF, MVLHF, and MVRHF images.…”
Section: D-mvahf-based Face Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent researches reported that classification accuracy can be enhanced through ensemble method. This method combines a set of weak learner models into a strong model [8] [9]. In machine learning paradigm, most popular ensemble strategies are Bagging, random subspace and boosting.…”
Section: Related Workmentioning
confidence: 99%
“…This technique exploit linear and polynomial kernel function. Aun Irtaza et al [9] offered a genetic algorithm (GA) primarily based classifier comity learning (GCCL) scheme to discover fixed classifiers because of combining ANN with SVMs by asymmetric and symmetric bagging algorithm.…”
Section: Machine Learning Paradigm Towards Content Based Image Retriementioning
confidence: 99%